Validation of Self-Esteem Instrument in Drug Use Prevention among Secondary School Students in Malaysia - Ahmad Jazimin Jusoh; Suzaily Wahab; Siti Zobidah Omar; Nazre Abdul Rashid (Universitas Negeri Padang, 2026)
There is an exact instrument that measures global self-esteem. However, there is no instrument that relates self-esteem with drug abuse tendencies. Therefore, this paper presented the validation of self-esteem in drug use instruments among secondary school students in Malaysia. This research was a survey-design by using quantitative technique for data analysis. The survey questionnaire was distributed to several schools by targeting secondary school students. In the end, 220 students from Johor, Selangor and Kuala Lumpur participated in the research. Factorial analysis, namely exploratory factor analysis (EFA) and Confirmatory factor analysis (CFA) conducted. The analysis was complemented with parallel analysis and Minimum Average Partial (MAP). The original and revised MAP tests confirm three factors for the instrument: peer self-esteem, home self-esteem, and school self-esteem. CFA was used to validate the structure and inspect the construct validity. The result showed that the instrument gains the acceptable value in several goodness indices such as GFI, AGFI, CFI, TLI, NFI, RMSEA, and CMIN.